Mrs. Frisby and the rats of NIMH - O'Brien, Robert C.; Bernstein, Zena (New York : Aladdin Paperbacks, 1986)
With nowhere else to turn, a field mouse asks the clever escaped lab rats living under the rosebush to help save her son, who lies in the path of the farmer's tractor, too ill to be moved.
"Aladdin fantasy"--Cover.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Booklist, September 2007.
Bulletin (Center for Children's books), July 2007.
Keywords: Mice -- Fiction; Rats -- Fiction; Mice -- Fiction; Rats -- Fiction